Is Sonchus arvensis Capable of Further Expanding in Germany? - Assessing the Potential by Combining Literature Data with Plant Metric Data - Defant, F. C.; Ganji, E.; Andert, S.; Salonen, Jukka; Tørresen, K. S.; Gerowitt, B. (Springer Science and Business Media LLC, 2026)
Research on Sonchus arvensis L. is underrepresented despite its status as a widespread perennial arable weed in the Northern Hemisphere. This study investigates, based on a comparison of literature data and recent plant metric data, whether there are indications of a problematic expansion in Germany and identified two knowledge gaps. The recent plant metric data were taken between 2019–2024 at various sites in Germany, Norway, and Finland. We structured the results in subchapters along the life-stages of S. arvensis given in their headings: ‘Propagules in the soil’, ‘Plant establishment’, ‘Rosette growth’, ‘Plant height’, ‘Seed production’ and ‘Plant senescence’. In Germany, S. arvensis has a rosette diameter measuring 34–58 cm and a height of 40–98 cm, although a height of up to 220 cm has been recorded in 2024 in Germany. Rosette diameter and plant height data indicate at least no smaller sizes compared to studies and plant metric data from other countries. Notably, 142 seeds per head were counted in Germany, indicating a source for successful spatial spreading. We address two knowledge gaps related to the research question in the title. One regarding whether vegetative growth contributes to the spread of S. arvensis, and another concerning how its phenological development is influenced by temperature and photoperiod. In addition, we recommend monitoring the species biology and ecology on agricultural fields in Germany.
Keywords: perennial sow-thistle; perennial plant; plant distribution; weed biology